Segmentation of the middle eastern and chinese tourists in Malaysia - Lee, Xin Nie; Teo, Wee Wing; Wang, Shin Cheng (2017)
Knowing the differences and s imilarities in the two groups of Middle Easterners and China tourists is crucial to provide information for those related in the tourism industry. The purpose of this study is to find the differences and similarities in the demographics, behaviour, psychology, level of satisfaction, revisit intention, and recommendation of the two groups. Test was adopted to determine the significance of the two groups. Reliability test was conducted to determine the reliability of the satisfaction factor items asked in the survey questionnaire. Pearson Correlation Coefficient was adopted to examine the relationship between overall satisfaction and revisit intention, and between overall satisfaction and recommendation. Results of the analysis were positive in relationship between the variables, in which they are also significant. Differences and similarities between the two groups of respondents are also discussed. Researchers also provided suggestions to improve the Malaysian tourism industry and for future researches to further develop the research scope.